2009
DOI: 10.1086/600045
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease among Adults: Associations among Serotypes, Disease Characteristics, and Outcome

Abstract: The serotype appeared to be independently associated with IPD severity in adults, which indicates that careful monitoring of IPD after implementation of conjugate vaccines is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
101
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 13 publications
13
101
2
5
Order By: Relevance
“…This serotype-specifi c difference in disease potential has also been shown for mucosal infections, although the differences between serotypes were less apparent compared with differences in invasive potential (33). In addition, serotypes are independently associated with IPD severity (34,35). Harboe et al showed that highly encapsulated and frequently carried serotypes such as 11A, 10A, and 19A have high mortality rates among healthy persons >5 years of age that are comparable to PCV7 serotypes such as 19F or 6B.…”
Section: Discussionmentioning
confidence: 75%
“…This serotype-specifi c difference in disease potential has also been shown for mucosal infections, although the differences between serotypes were less apparent compared with differences in invasive potential (33). In addition, serotypes are independently associated with IPD severity (34,35). Harboe et al showed that highly encapsulated and frequently carried serotypes such as 11A, 10A, and 19A have high mortality rates among healthy persons >5 years of age that are comparable to PCV7 serotypes such as 19F or 6B.…”
Section: Discussionmentioning
confidence: 75%
“…The reported estimated mortality associated with invasive pneumococcal disease varies from 7 to 43%, depending on pneumococcal serotype, medical history of the patient, and many other factors (2,12,14). Community-acquired pneumonia (CAP) is one of the most common causes of death worldwide and the leading cause of death by infection in the United States (9,13,19).…”
mentioning
confidence: 99%
“…The capsular polysaccharide of S. pneumoniae is known to be an important factor in the pathogenicity of the organism (7), and associations of the capsular serotypes with the severity of invasive pneumococcal diseases (IPDs) have been described (2,14). IPDs are known to be much more frequent among young children and elderly persons than among older children and middle-aged adults (25).…”
mentioning
confidence: 99%